Jurnal Hukum Makna Asas Legalitas Sebagai Pengakuan Terhadap Hukum Pidana Adat dan Penerimaan Norma-Norma Hukum Tradisonal - Sigit Kamseno (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Standard criminal regulation is a general set of laws that develops and creates among native networks with rules that are unique in relation to general criminal regulation. One of the rules that is the fundamental premise in standard criminal regulation is the guideline of lawfulness.This standard underscores the significance of having areasonable legitimate premise in deciding aq go about as a crook act and in monumental lawbreakers sanctions.